PENERAPAN ASAS TABELLIONIS OFFICIUM FIDELITER EXERCEBO DALAM PENANDATANGANAN AKTA NOTARIS SECARA DIGITAL - Kartika, Rifda Salma; Lintang Saskia Salsabella; Angelica Ratih Kusumadewi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2024)
The development of information and communication technology requires the law to move dynamically along with developments in time and technology. There is a principle used by Notaries in carrying out their duties and positions, namely the Tablelionis Officium Fideliter Exercebo Principle, the principle which states that Notaries must work traditionally. There is a problem formulation, namely the Influence of Digital Signatures on the Obligations and Authorities of Notaries Based on the Tablelionis Officium Fideliter Exercebo Principle. The approach used is a statutory approach (statue approach) and a contextual approach (conceptual approach). The basis for applying digital signatures is contained in article 1 number 12 of the ITE Law and article 1 number 22 of PP PSTE which has legal force and legal consequences, at the General Meeting of Shareholders (GMS) carried out virtually. Digital signatures in e-rups have fulfilled the requirements in the ITE Law. Making e-rups by a Notary must also not violate the principle of the principle of the Tablelionis Officium Fideliter Exercebo principle.